Valorization of banana peel for citric acid production under solid state fermentation with aspergillus Niger - Chysirichote, T. (My University, 2020)
Valorization of banana peel (BP) through solid state fermentation (SSF) was aimed in this research. The appropriate conditions of citric acid (CA) production by SSF of Aspergillus Niger were investigated. Firstly, the optimum initial pH of the BP and the aeration rate were studied by conducting SSF in a 250-mL flask and 2-L glass column, respectively. It was found that the initial pH of the BP and aeration rates affected the CA production. The results showed that the initial pH of 5.0 and 1.0 vvm aeration were appropriate for the CA production of A. Niger using BP as a substrate. The problem of rising temperature during SSF was found when applying the optimum condition to the SSF in the 20-L packed bed bioreactor (PBB), which caused a decrease in the CA production compared to that of the glass column. The cooling air jacket constructed to the PBB to remove the heat during the SSF helped increase the CA production from that in the PBB. The maximum CA production in the 20-L air-jacketed PBB was 124.0±19.2 mg g-1DS.
Keywords: Aspergillus Niger; Banana peel; Citric acid; Packed bed bioreactor; Solid-state fermentation